2014
DOI: 10.1111/hsc.12093
|View full text |Cite
|
Sign up to set email alerts
|

Women's strategies to achieve access to healthcare in Ontario, Canada: a meta-synthesis

Abstract: As part of a mixed methods study on women's access to the healthcare system in Ontario, Canada, we undertook a qualitative meta‐synthesis to better understand the contextual conditions under which women access healthcare. An earlier phase of the synthesis demonstrated a series of factors that complicate women's access to healthcare in Ontario. Here, we consider women's agency in responding to these factors. We used meta‐study methods to synthesise findings from qualitative studies published between January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 68 publications
1
20
0
1
Order By: Relevance
“…Lombardo, who was not involved in the initial analytic process, subsequently read all of the articles. He confirmed that the metadata analysis was consistent with the content of the articles, and then conducted a further analysis that was focused on the representation of women’s health-seeking activities (Lombardo et al, 2012).…”
Section: Methodsmentioning
confidence: 71%
“…Lombardo, who was not involved in the initial analytic process, subsequently read all of the articles. He confirmed that the metadata analysis was consistent with the content of the articles, and then conducted a further analysis that was focused on the representation of women’s health-seeking activities (Lombardo et al, 2012).…”
Section: Methodsmentioning
confidence: 71%
“…Access to health services has been the focus of research, policy and practice for several decades (Lombardo et al, ). According to Vaarama (), good access to appropriate care and help is necessary for older people, but the psycho‐social dimensions of QoL also need more attention.…”
Section: Discussionmentioning
confidence: 99%
“…; Rhodes & Treloar ; Banning ; Lombardo et al . ). In case of discrepancy, a third reviewer was consulted.…”
Section: Methodsmentioning
confidence: 97%